Nucleotide sequence of afsB, a pleiotropic gene involved in secondary metabolism in Streptomyces coelicolor A3(2) and "Streptomyces lividans". - Horinouchi, S (1986)
The nucleotide sequence of afsB from Streptomyces coelicolor A3(2), a pleiotropic gene which positively controls the biosynthesis of A-factor and the pigmented antibiotics actinorhodin and undecylprodigiosin in S. coelicolor A3(2) and "Streptomyces lividans," was determined. The determinant of the afsB gene, which includes the putative AfsB protein consisting of 243 amino acids, was mapped functionally by tests for A-factor and pigment production in "S. lividans" and S. coelicolor A3(2) after introduction of recombinant plasmids containing various restriction endonuclease fragments on the vector plasmids pIJ41 and pIJ702. The putative AfsB protein contains two regions separated by 167 residues which resemble conserved domains of known DNA-binding proteins. High-resolution nuclease S1 protection mapping revealed that the afsB mRNA, approximately 1,300 base pairs (bp) long, which was determined by Northern blot hybridization, had its start point 340 bp upstream of the putative methionine start codon. The Northern hybridization experiment also suggested that the afsB gene was constitutively transcribed throughout growth. Also shown by the Northern hybridization was the presence of an unidentified gene with an extraordinary amount of 880-bp mRNA located downstream from afsB. Dot hybridization with the brown pigment production genes, possibly involved in polyketide biosynthesis, as the probe suggested that the afsB gene did not stimulate transcription of the pigment production genes. In Southern blot DNA-DNA hybridization analysis with the afsB sequence as the probe, sequences exhibiting various degrees of homology were found in several Streptomyces spp. A DNA sequence showing strong homology to the afsB in Streptomyces griseus FT-1, a high streptomycin producer, behaved like an extrachromosomal element, homologous to the afsA gene, a structural gene for A-factor biosynthesis.